Educational Public Relations Strategies in Improving an Institutional Image - Ali Mabrur; Hefniy Hefniy (Journal of Research in Educational Management, 2024)
The aim of this journal article is to investigate public relations strategies at MI Miftahul Ulum Jurang with a focus on understanding conventional and modern approaches. Against the backdrop of increasing digitalization and the need for effective stakeholder engagement, this research explores how educational institutions navigate the complexities of public relations to build trust and improve institutional image at MI Miftahul Ulum Jurang. The research method used is descriptive qualitative with data collection through interviews, observation and documentation to collect data. Triangulation of data sources as analysis allows for a comprehensive understanding of the public relations strategies used. Research findings reveal that there is a dual approach in public relations at MI Miftahul Ulum Jurang, namely conventional methods which include face-to-face interactions and door-to-door visits, as well as modern methods which include social media platforms such as YouTube, Facebook and Instagram. as physical publications such as banners and billboards. Through the lens of personal branding and public trust, this study highlights the importance of consistent and attractive communication through both conventional and modern channels in shaping an institutional image and growing stakeholder trust. This research offers valuable insights for educational practitioners and scholars who wish to improve the understanding and practice of public relations in educational contexts.